Severity and type of lymphoma are associated with aortic 18-fluorodeoxyglucose (FDG) positron emission tomographic uptake assessed by FDG PET/CT imaging. (25th November 2020) - Koutagiar, I; Georgakopoulos, A; Pouli, A; Sioni, A; Giannouli, S; Solomou, E; Terentes-Printzios, D; Karakitsios, I; Kafouris, P; Gaitanis, A; Petrocheilou, A; Pianou, N; et al.
Abstract: Introduction: There is increasing evidence that metabolic disease burden in lymphoma influence patients' outcome.However, the impact of disease severity on cardiovascular system remains unknown. Purpose: To assess whether lymphoma is associated with arterial inflammation by examining the relationship between disease metabolic burden and arterial fluorodeoxyglucose (FDG) uptake. Methods: Sixty-two patients (43 male, mean age 58±18 years) with Hodgkin (n=29) or non-Hodgkin lymphoma (n=33) before chemotherapy and two separate control groups of 14 and 16 healthy individuals for Hodgkin and non-Hodgkin population respectively, with similar age, sex and cardiovascular risk factors, underwent FDG position emission tomography (FDG-PET/CT) imaging.Disease severity was quantified by metabolic tumor volume (MTV) and total lesion glycolysis (TLG) corresponding to standard uptake values (SUV) ≥41% or ≥2.5 of maximum SUV within lymphoma regions, and aortic FDG uptake by target-to-background ratio (TBR). Serum high sensitivity-C-reactive protein (hs-CRP), white blood count (WBC), ratio of neutrophils to lymphocytes (N/L), albumin and lactic acid dehydrogenase (LDH) values were measured for patient group. Results: MTV and TLG measurements correlated significantly with hs-CRP, WBC, N/L ratio, albumin and LDH table 1.Patients with non-Hodgkin or Hodgkin lymphoma had increased aortic TBR compared to controls (p=0.001 and p=0.023, respectively).Aortic TBR was higher in patients with stage III-IV disease compared to those with stage I-I (p=0.046).There were significant associations between aortic FDG uptake and MTV values, which remained significant after adjustment for confounders (β=0.353, p=0.001, adjusted R2=0.318 for MTV41%, β=0.442, p=0.001, adjusted R2=0.269 for MTV2.5), Figure 1. Conclusions: Aortic wall FDG uptake is related with disease severity indicating a vascular effect of lymphoma, as well as a new potential role of molecular imaging in cardio-oncology for evaluating disease severity and its consequences to vascular beds with a single examination. Funding Acknowledgement: Type of funding source: None